2022
DOI: 10.23736/s2724-5691.21.08851-1
|View full text |Cite
|
Sign up to set email alerts
|

Repercussions of COVID-19-related national lockdown on Emergency Surgery Department: a longitudinal cohort monocentric study

Abstract: The final version may contain major or minor changes.Subscription: Information about subscribing to Minerva Medica journals is online at: http://www.minervamedica.it/en/how-to-order-journals.php Reprints and permissions: For information about reprints and permissions send an email to:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“… 49 An international cohort study across 40 countries observed a shorter hospital-LOS and higher mortality in elective colorectal cancer surgery during the COVID-19 pandemic. 54 Other studies in Greece, 13 the United Kingdom, 39 Russia, 55 and Italy 56 also observed increased mortality during COVID-19. In a scoping review, it was observed that there was a delay in patients seeking care in emergency general surgeries, but it was impossible to conclude that there were more complications or increased mortality during the pandemic.…”
Section: Discussionmentioning
confidence: 90%
“… 49 An international cohort study across 40 countries observed a shorter hospital-LOS and higher mortality in elective colorectal cancer surgery during the COVID-19 pandemic. 54 Other studies in Greece, 13 the United Kingdom, 39 Russia, 55 and Italy 56 also observed increased mortality during COVID-19. In a scoping review, it was observed that there was a delay in patients seeking care in emergency general surgeries, but it was impossible to conclude that there were more complications or increased mortality during the pandemic.…”
Section: Discussionmentioning
confidence: 90%